The Association of Junk Food Consumption with Preadolescents' Environmental Influences: A School-Based Epidemiological Study in Greece - Ioannis Gketsios; Thomas Tsiampalis; Alexandra Foscolou; Tonia Vassilakou; Aikaterini Kanellopoulou; Venetia Notara; George Antonogeorgos; Andrea Paola Rojas-Gil; Ekaterina N. Kornilaki; Areti Lagiou; Demosthenes B. Panagiotakos; Rena I. Kosti (MDPI AG, 2022)
The aim of the present study was to evaluate the impact of environmental influences on Greek preadolescents' junk food consumption. A cross-sectional study, was conducted among 1718 preadolescents (mean (standard deviation(SD)) age: 11.2(0.8) years old; 54% girls) and their parents, during the school years 2014-2016. Parental and child characteristics were collected anonymously, through self-administered and validated questionnaires. Among others, junk food consumption was recorded, classifying children as low, moderate, and high consumers. The majority of the preadolescents were classified as at least moderate junk food consumers, while almost 3/10 children were classified as high junk food consumers. A significantly lower junk food consumption was observed among preadolescents with a healthier family environment, consisting of normal-weight parents who consume junk foods less frequently, prefer home-cooked meals and adhere more to the Mediterranean diet, while more frequent family meals were also associated with lower junk food consumption. In addition, influence from teachers and participation in extracurricular sports activities were significantly associated with lower junk food consumption, while advertisements were found to have a significant negative impact on preadolescents' eating habits. Notwithstanding, peers were not found to influence their dietary choices in terms of junk food consumption. Both parents and teachers seem to be positive influencers on preadolescents' low junk food consumption. The detrimental role of advertisements on junk food consumption is reconfirmed, while peers' influence is not significant on junk food consumption. The need for urgent public health initiatives for the promotion of healthy dietary habits among preadolescents is warranted.